1890 La. Acts 39 - (:unkn) unknown (My University, 1890)
Ch. 46: Prohibiting the transfer of any pistol, dirk, Bowie knife, or "any other dangerous weapon, which may be carried concealed on a person to any person under the age of 21.
Keywords: TRANSFER - MINORS